Characteristics of different types of Helicobacter pylori: New evidence from non-amplified white light endoscopy - Liu, Weidong; Kong, Wenjie; Hui, Wenjia; Wang, Chun; Jiang, Qi; Shi, Hong; Gao, Feng (Frontiers in Microbiology, 2023)
Background Different types of Helicobacter pylori (H. pylori) were analyzed to determine their infection characteristics using serology, pathology, and non-magnification white light endoscopy combined with the Kimura–Takemoto classification, and the regular arrangement of collecting venules (RAC) as well. Materials and methods A retrospective analysis of 685 inpatients who have completed the 14C-urea breath test, the H. pylori antibody typing classification, the serum gastric function tests (PGI/PGII/G-17), the endoscope detection, and the pathological examinations. Results The levels of PGI, PGII, and G-17 were in descending order from the type I H. pylori infection group to the type II H. pylori infection group than the control group (F = 14.31; 26.23; 9.12, P < 0.01). Using the Kimura–Takemoto classification, there were significant differences among the three groups of different degrees of atrophy (χ2=29.81; 482.78; 292.5, P< 0.01). Based on the characteristics of RAC, the H. pylori infection rates were in descending order from the type I H. pylori infection group to the type II H. pylori infection group than the control group (χ2= 200.39; 174.72; 143.51, P < 0.01). The type I H. pylori infection group had higher grades than those of the type II H. pylori infection group in the OLGA and OLGIM staging systems, while the differences are statistically significant only in the OLGA staging system (χ2=10.63, P < 0.05). Conclusion With the aid of non-amplified white light endoscopy, we found new evidence of type I H. pylori infection accelerating the progression of gastric mucosal atrophy through the degree of atrophy and the range of infection, whereas type II H. pylori infection has a low ability of migration and atrophy progression. Individual virulence factor-based eradication therapy may be a better choice in future.